When knowledge is not enough: the role of attitude in anemia preventive behavior among adolescents - Ledy Ervita; Wulida Litaqia; Devi Harmita; Yusriani Saleh Baso; Hanafi Hanafi (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2026)
Introduction: Adolescent anemia remains a significant public health concern affecting physical growth, cognitive performance, and long-term productivity. Despite ongoing school-based iron supplementation programs, preventive behaviors remain suboptimal. Behavioral determinants, particularly within the Knowledge Attitude Practice (KAP) framework, may explain this gap. This study aimed to identify factors associated with anemia preventive behavior among adolescents and to determine which behavioral determinant independently predicts preventive practice. Research Methodology: A quantitative cross-sectional study was conducted among 84 12th-grade students in West Kalimantan, Indonesia. Data were collected using a validated 15-item KAP questionnaire adapted from FAO guidelines. Descriptive statistics were applied, followed by Chi-square and Fisher’s Exact tests. Binary logistic regression was performed to identify independent predictors, with p < 0.05 as the threshold for statistical significance. Results: Most respondents demonstrated good knowledge (89.3%), positive attitudes (91.7%), and good preventive practices (70.2%). Bivariate analysis showed that attitude was significantly associated with preventive practice (p = 0.012), whereas knowledge was not (p = 0.293). Multivariate analysis confirmed that attitude remained the only independent predictor (OR = 6.624; p = 0.033). Adolescents with positive attitudes were 6.6 times more likely to demonstrate good preventive behavior. Conclusion: Attitude was independently associated with anemia-preventive behavior, whereas knowledge alone did not significantly influence practice. These findings imply that school-based and nursing interventions should prioritize strengthening positive attitudes and motivational engagement to promote sustainable anemia prevention behaviors.